Search for $B^0_s \to \mu^+ \mu^-$ and $B^0 \to \mu^+ \mu^-$ decays - CMS collaboration (2205 authors); Hollar, Jonathan; Nayak, Aruna; Almeida, Nuno; Bargassa, Pedrame; David Tinoco Mendes, Andre; Faccioli, Pietro; Ferreira Parracho, Pedro Guilherme; Gallinaro, Michele; Seixas, Joao; Varela, Joao; Vischia, Pietro; et al. (My University, 2012)
A search for the rare decays B_s to mu+ mu- and B^0 to mu^+ mu^- is performed in pp collisions at sqrt(s) = 7 TeV, with a data sample corresponding to an integrated luminosity of 5 inverse femtobarns collected by the CMS experiment at the LHC. In both decays, the number of events observed after all selection requirements is consistent with the expectation from background plus standard model signal predictions. The resulting upper limits on the branching fractions are Br(B_s to mu^+ mu^-) < 7.7E-9 and Br(B^0 to mu^+ mu^-) < 1.8E-9 at 95% confidence level.